Comparative Study of Western Fitness Exercises and Traditional Chinese Health Preserving Exercises from the Perspective of Cultural Ideals - Han, Cui Yi; Li, Sheng (The Journal of the International Society of Chinese Health Practices, 2024)
Abstract: Research Objective: This study aims to investigate the interplay between economy and culture, recognizing that economic factors shape the development of culture while culture, in turn, exerts influence on economic development. The current strategic focus in our country is on becoming a strong cultural nation, as emphasized in the 20th National Congress by the Party with respect to two key strategies: "Advancing cultural self-confidence and strength to forge a new era of socialist cultural brilliance" and "Extensively promoting nationwide fitness activities, strengthening youth sports initiatives, fostering comprehensive development of mass sports and competitive sports, and accelerating the construction of a sports powerhouse." Chinese President Xi Jinping has also highlighted the importance of sports development, stating that it not only constitutes a significant aspect of realizing the Chinese Dream but also provides a powerful spiritual impetus for the great rejuvenation of the Chinese nation. Upholding the spirit of Chinese sports, promoting sports ethics, and facilitating the coordinated development of mass sports, competitive sports, and the sports industry are imperative in our pursuit of constructing a sports powerhouse. In light of these considerations, the establishment of a fitness culture assumes increasing significance. Adopting an East-West cultural ideals perspective, this paper employs research methods such as literature review, comparative analysis, and logical analysis to investigate the distinctions between Western fitness exercises and traditional Chinese health-preserving exercises. The findings of this study aim to propel the development of sports culture and its related endeavors. Research Methods:1. Literature Review: A comprehensive literature review was conducted utilizing official library websites such as Shandong Sports University Library and the National Library of China, as well as academic platforms like CNKI (China National Knowledge Infrastructure) and Wanfang Database. Key search terms such as "Western fitness exercises" and "traditional Chinese health-preserving exercises" were employed to gather relevant books, publications from core journals, and scholarly articles to provide theoretical support for this research. 2. Expert Interviews: Interviews were conducted with experts and scholars in relevant fields to gather insights into Western fitness exercises and traditional Chinese health-preserving exercises, including their origins and historical development. 3. Logical Analysis: The collected materials were systematically organized and analyzed to form the main content of this research. 4. Comparative Study: A comparative analysis was conducted to compare Western fitness exercises with traditional Chinese health-preserving exercises, resulting in the findings and conclusions of this study. Research Results: Cultural Ideals in Western Fitness Exercises: (1) Educational Cultural Ideals: Western fitness exercises originated from education. The ancient Greek philosopher and thinker Plato equated physical education with intellectual education. During the period of Solon's reforms, the status of sports was elevated, and it was considered a means of cultivating talent along with moral, intellectual, and aesthetic education. The fitness industry in Athens also experienced certain development during this time, and the English word "academy" in higher education originated from a gymnasium in Athens. In the modern era, influenced by the Renaissance and the Enlightenment movement, fitness exercises developed in a more scientific and humanistic direction. Knightly training and Greek-style fitness methods gained recognition and importance from philosophers and educators, playing a significant role in the history of physical education. (2) Military Training Ideology: Western fitness exercises have had military functions since their inception. The city-state of Sparta had a primarily military nature, and its extreme military fitness training, while enhancing the physical abilities, fitness, and combat readiness of its inhabitants, had certain negative effects on social development due to its neglect of intellectual education. Athens also conducted military training through fitness exercises to cultivate military personnel who possessed both literary and martial skills. However, it was limited to adult male citizens of the city-state, neglecting women and hindering social development. In the modern era, with the evolving global situation, the military functions of fitness exercises gradually gained prominence in various European and American countries. Prominent German physical education teacher Friedrich Ludwig Jahn established the Jahn gymnastics system, which had certain influence on later events such as the Franco-Prussian War. Swedish writer, poet, and educator Pehr Henrik Ling developed military gymnastics based on theories like anatomical studies, which included the Ling system of gymnastics used for military training, contributing to the physical and mental development of soldiers. (3) Scientific Theories and Ideas, including Anatomy: Starting from the Enlightenment period, scientific ideas such as exercise anatomy have played a significant role in the development of Western fitness exercises. Influenced by disciplines such as exercise anatomy and sports psychology, Western fitness exercises have undergone scientific development. Whether it is changes in physique, improvements in physical fitness, release of psychological stress, or enhancement of mental well-being, Western fitness exercises have positive implications.2. Cultural Ideals in Traditional Chinese Health-Preserving Exercises: (1) Philosophical Ideas of Laozi and the Book of Changes (Zhouyi): The emergence of traditional Chinese health-preserving exercises is closely related to the philosophical ideas of Laozi and the Book of Changes. On one hand, the philosophy of Laozi emphasizes the role of natural laws, stillness for nurturing life, and the unity of form and spirit in health preservation. On the other hand, the Book of Changes emphasizes the dialectical unity of yin and yang as well as movement and stillness. As a result, traditional health-preserving exercises are characterized by relatively slow movement speeds and gentle rhythms, which contribute to comprehensive adjustments of the body. (2) Ideals from Tai Chi and Other Martial Arts Schools: Martial arts-based health preservation is the outcome of the integration of traditional health-preserving exercises with martial arts. Chen-style Tai Chi Chuan, for example, was developed by Chen Wangting based on Qu Jiguang's "Thirty-Two Styles of Fist" combined with skills such as guided energy techniques. It plays a crucial role in regulating the body's energy and blood circulation. Shaolin Zen Martial Medicine emphasizes the role of nourishing Qi (vital energy), asserting that whether practicing martial arts or acquiring certain skills, one must first nourish Qi. By prioritizing the cultivation of Qi, all other endeavors become more efficient. Additionally, it emphasizes the combination of Zen meditation and health-preservation methods in bringing about physiological and psychological changes. (3) Traditional Chinese Medicine Theories such as Yin-Yang and Five Elements: The relevant theories of traditional Chinese medicine provide guidance for traditional health-preserving exercises. The Yin-Yang and Five Elements theories suggest that the human body consists of the interaction of Yin and Yang as well as the five elements of metal, wood, water, fire, and earth. These elements correspond to the body's five viscera, five bowels, and five flavors. Health can only be achieved when there is relative harmony between Yin-Yang and the Five Elements. This theory also forms the foundation for the creation of the Five Animal Frolics exercise. The theory of Heavenly Stems and Earthly Branches divides a day into twelve segments, each associated with specific organs and their functions. Adhering to these principles is essential for maintaining the normal functioning of the body. The theory of meridians divides the human body into twelve meridians, eight extraordinary meridians, and 720 acupoints. These acupoints and meridians connect various organs and tissues in the body. Stimulating specific acupoints is beneficial for treating certain diseases. The creation of the Da Wu dance is based on the theory of meridians in traditional Chinese medicine. Research Conclusion: Based on the aforementioned content, the following differences between Western fitness exercises and traditional Chinese health-preserving exercises can be identified:(1) Origins: Western fitness exercises originated from education, primarily focusing on cultivating moral qualities through external factors such as teachers. On the other hand, traditional Chinese health-preserving exercises trace their roots back to the philosophical ideas of Laozi and the Book of Changes, emphasizing self-cultivation and inner transformation to shape individuals' moral and values systems. As a result, traditional Chinese health-preserving exercises place relatively greater emphasis on the role of internal factors such as psychology and emotions in effecting personal change.(2) Functional Aspects: In addition to its educational function, Western fitness exercises also have a certain military function, significantly influencing the physical fitness of soldiers and the combat effectiveness of military units. The integration of traditional martial arts contributes to the development of certain combat skills within traditional health-preserving exercises. Furthermore, traditional health-preserving exercises draw guidance from theories in traditional Chinese medicine, thus possessing certain therapeutic functions.(3) Theoretical Orientations: Western fitness exercises are guided by theories of exercise anatomy, exercise physiology, and sports psychology. They emphasize the use of high-intensity exercise to promote physical and mental well-being. In contrast, traditional Chinese health-preserving exercises are rooted in the theories of traditional Chinese medicine, emphasizing not only the effects of physical exercise but also the importance of lifestyle habits. Compared to Western fitness exercises, traditional Chinese health-preserving exercises tend to take a more holistic approach.